Aspect in grammatical variation - Walker, James A. (James Anthony) (Studies in language variation, 2010)
The articles in this edited volume represent a range of approaches to studying the role of verbal aspect in grammatical variation. Issues addressed include: defining the variable context; operationalizing aspectual distinctions as factors conditioning linguistic variation; and the appropriate number of aspectual distinctions and levels. Apart from bringing to light various methodological and analytical issues, this volume gathers together a unique collection of original research, based on spoken- and written-language corpora, of an array of languages and linguistic varieties: African American.